2017
DOI: 10.15740/has/au/12.1/169-171
|View full text |Cite
|
Sign up to set email alerts
|

Economic impact of front line demonstrations on finger millet yields

Abstract: A study was conducted for two years during 2014-15 and 2015-16 involving 30 and 15 farmers at Tumkur and Ramanagara districts, respectively. The improved finger millet variety KMR-301 and KMR-204 were used to demonstrate the improved production technology on finger millet in the farmer's field. The data revealed that during 2014 by the introduction of new technology the grain yield was increased by 36 per cent over farmers practice and during 2015, at Ramanagara district the yield improvement was to the tune o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
0
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
2
0
0
Order By: Relevance
“…Hence, the productivity of finger millet might be increased by growing suitable variety along with improved crop management practices. Similar studies on crop yield increase by adoption of improved crop management practices were reported by Subhashree et al (2017) in Finger millet; Sharma et al (2016) and Singh (2017) in Wheat; Jat and Gupta (2015) in Pearl millet; Meena et al, (2014) in Maize. Considering the above facts, a frontline demonstration was proposed and conducted in the farmers' holdings to demonstrate the improved package of practices for higher productivity in finger millet under rainfed condition.…”
Section: Introductionsupporting
confidence: 72%
“…Hence, the productivity of finger millet might be increased by growing suitable variety along with improved crop management practices. Similar studies on crop yield increase by adoption of improved crop management practices were reported by Subhashree et al (2017) in Finger millet; Sharma et al (2016) and Singh (2017) in Wheat; Jat and Gupta (2015) in Pearl millet; Meena et al, (2014) in Maize. Considering the above facts, a frontline demonstration was proposed and conducted in the farmers' holdings to demonstrate the improved package of practices for higher productivity in finger millet under rainfed condition.…”
Section: Introductionsupporting
confidence: 72%
“…Hence, the productivity of finger millet might be increased by growing suitable variety along with improved crop management practices. Similar studies on crop yield increase by adoption of improved crop management practices were reported by Subhashree et al, (2017) in Finger millet; Sharma et al, (2016) and Singh (2017) in Wheat; Jat and Gupta (2015) in Pearl millet; Meena et al, (2014) in Maize. Considering the above facts, a frontline demonstration was proposed and conducted in the farmers' holdings to demonstrate the improved package of practices for higher productivity in finger millet under rainfed condition.…”
Section: Introductionsupporting
confidence: 70%